Evaluation of Open-Source Application Utilization for Enhancing Learning Quality - Ihdalhubbi Maulida; Syahmani; Musyifa Adla (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
Open-source software serves as a source of software that requires little cost, making this application easy to modify and independently develop. The Computer Education Study Program improves practical learning with the use of Open-source software, aiming to measure the effectiveness of open-source software in the practical learning conducted in the laboratory of the Computer Education Study Program. The effectiveness of open-source software was measured using a research and development method approach to determine that the open-source software can be applied to laboratory-based learning, and a survey approach using Likert scale to evaluate students' understanding of open-source software applications. The open-source software that was measured for effectiveness includes NetBeans for the Basic Programming II course, Visual Studio Code for the Web Programmers I and II Course, MATLAB for the Simulation and Modeling Course, and the use of Linux for the Operating System Course. The data sample consisted of 39 students in the Computer Education Study Program. The effectiveness was assessed in the implementation of open-source practicum learning was assessed by collecting supporting open-source software data, validating open-source software, simulating practicum on software in lecture materials, and conducting practicum material trials in real classroom practicum lectures. Based on the results of the trial, it was found that 85% of the open-source software can be used in lectures, and 80% of students were able to understand how to use the open-source software.